2015
DOI: 10.1186/s12966-015-0211-7
|View full text |Cite
|
Sign up to set email alerts
|

HOME Plus: Program design and implementation of a family-focused, community-based intervention to promote the frequency and healthfulness of family meals, reduce children’s sedentary behavior, and prevent obesity

Abstract: BackgroundInvolvement in meal preparation and eating meals with one’s family are associated with better dietary quality and healthy body weight for youth. Given the poor dietary quality of many youth, potential benefits of family meals for better nutritional intake and great variation in family meals, development and evaluation of interventions aimed at improving and increasing family meals are needed. This paper presents the design of key intervention components and process evaluation of a community-based pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
60
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 45 publications
1
60
0
1
Order By: Relevance
“…According to these studies, a family mealtime surpasses the field of sensory experiences with food and in favor of a normal BMI and healthy eating habits (greater intake of FV, proteins, sources of calcium and lower consumption of sweets and sugar-sweetened beverages), family bonding and self-regulation of the appetite. 8,21,18,7,20,19,12,17 …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…According to these studies, a family mealtime surpasses the field of sensory experiences with food and in favor of a normal BMI and healthy eating habits (greater intake of FV, proteins, sources of calcium and lower consumption of sweets and sugar-sweetened beverages), family bonding and self-regulation of the appetite. 8,21,18,7,20,19,12,17 …”
Section: Discussionmentioning
confidence: 99%
“…Flattum et al 8 developed a program called Healthy Home Offerings via the Mealtime Environment (HOME Plus), to prevent obesity, applied in 81 American families (children aged 8 to 12 years old and their parents) in a ten 2h-sessions, and five motivational phone calls to promote healthy eating habits and to increase family mealtime. After the interventions of HOME program, 87% of the parents reported that their children were more receptive in trying new food, 52% of the children ate more FV, and 86% of the parents reported that their children were more aware of the portion sizes.…”
Section: Impact On the Food Qualitymentioning
confidence: 99%
See 3 more Smart Citations